The Radiotoxicity of 131I Therapy of Thyroid Cancer: Assessment by Micronucleus Assay of B Lymphocytes - Watanabe, Naoto; Kanegane, Hirokazu; Kinuya, Seigo; Shuke, Noriyuki; Yokoyama, Kunihiko; Kato, Hiroshi; Tomizawa, Gakuto; Shimizu, Masashi; Funada, Hisashi; Seto, Hikaru (The Journal of nuclear medicine (1978), 2004)
We investigated cytologic radiation damage in thyroid cancer after (131)I therapy using micronucleus assay (MNA) of B lymphocytes exclusively, as opposed to our previous study in which MNA of all lymphocyte subsets was used. We studied 22 thyroid cancer patients treated with 3.7 GBq of (131)I. Peripheral lymphocytes were harvested, and B lymphocytes were isolated by an immunomagnetic method and assayed for the frequency of micronuclei. The frequency of micronuclei among B cells after (131)I therapy was significantly increased relative to that in untreated control subjects, and the (131)I-induced increase in micronuclei frequency among B cells was significantly greater than that among all lymphocytes. Compared with the MNA of all lymphocytes, the MNA among specifically B cells may more sensitively detect cytologic radiation damage associated with (131)I therapy of thyroid cancer.